1997
DOI: 10.1051/aas:1997214
|View full text |Cite
|
Sign up to set email alerts
|

A large scale CO survey of the Galactic center region

Abstract: Abstract. We present the data from a CO(J = 1 → 0) survey of the central region of our Galaxy. The observations were obtained with the 1.2-m Southern Millimeter-wave Telescope at Cerro Tololo Interamerican Observatory, Chile. This instrument has a full beam-width at half maximum (FWHM) of 8.8 at 115 GHz, the frequency of the observed transition. The survey covers a strip 4• wide in latitude along the galactic equator in the range −12• ≤ l ≤ +13• . The spatial sampling interval was 7.5 (0.85 beam-widths) for |b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 13 publications
8
109
0
1
Order By: Relevance
“…It has been observed previously by several authors (Bitran et al 1997;Fukui et al 2006;Sawada et al 2001;Lee & Lee 2003;Riquelme et al 2010b); its main velocity component is at 98 km s −1 (from the HCO + data from Riquelme et al 2010b), and a large velocity width in all the species is observed in this and previous works, which indicates that this source indeed belongs to the GC region. …”
Section: Single Temperature Regime In the Loop Regionsupporting
confidence: 83%
“…It has been observed previously by several authors (Bitran et al 1997;Fukui et al 2006;Sawada et al 2001;Lee & Lee 2003;Riquelme et al 2010b); its main velocity component is at 98 km s −1 (from the HCO + data from Riquelme et al 2010b), and a large velocity width in all the species is observed in this and previous works, which indicates that this source indeed belongs to the GC region. …”
Section: Single Temperature Regime In the Loop Regionsupporting
confidence: 83%
“…The nature of these so-called wide line clouds has been discussed by Stacy et al (1988) and Kumar & Ri †ert (1997) ; the one at l \ 3¡, also known as Bania Clump 2, was discussed by Stark & Bania (1986). The southern telescope has mapped the Galactic center in both CO (Bitran et al 1997) and C18O (Dahmen et al 1997) ; other large-scale CO, 13CO, C18O, and CO (J \ 2È1) surveys of the Galactic center region are listed in Table 1 of Bitran et al (1997).…”
Section: Galactic Centermentioning
confidence: 99%
“…In conjunction with radio continuum, infrared, and optical observations of H II regions, OB associations, and other Population I objects, they have demonstrated that virtually all star formation occurs in molecular clouds, and highresolution CO observations of dense cloud cores and molecular outÑows have contributed greatly to our under- Dame et al 1987 ;(2) Bitran et al 1997 ;(3) Ungerechts et al 2000 ;(8) Huang & Thaddeus 1986 ;(9) Heithausen et al 1993 ; present work (778 additional scans in Polaris, 1738 in Camelopardalis) ; (10) S. T. Megeath, T. M. Dame, & P. Thaddeus, 2001, in preparation ; (11) Stacy & Thaddeus 1991 ;(12) Lang et al 2000 ;(13) Oliver et al 1996 ;(14) B. A.Wilson 2001b, in preparation ;(15) May et al, 1993 ;(16) J. May, D. C. Murphy, M. Sahu, H. Alvarez, & L. Bronfman, 2001, in preparation ;(17) Grabelsky et al 1987 ;(18) Boulanger et al 1998 ;(19) Nyman, Bronfman, & Thaddeus 1989 ;(20) Bronfman et al 1989 ;(21) de Geus, Bronfman, & Thaddeus 1990. standing of how stars form.…”
Section: Introductionmentioning
confidence: 96%
“…These results can be combined with CO data to provide insight into conditions A&A 523, A45 (2010) References. 1) Burton & Liszt (1983); 2) Jaffe et al (1996); 3) Nakagawa et al (1995); 4) Bania (1986); 5) Bitran et al (1997); 6) Fukui et al (2006); 7) Oka et al (1996); 8) Sawada et al (2001); 9) Oka et al (2007); 10) Bally et al (1987); 11) Dahmen et al (1997); 12) Morris et al (1983); 13) Martín-Pintado et al 199714) Boyce & Cohen (1994); 15) Zylka et al (1992); 16) Fukui et al (1977); 17) Jackson et al (1996); 18) Lee (1996). Notes.…”
Section: Introductionunclassified
“…Large-scale surveys have been made in 12 C 16 O and its isotopomers in the J = 1 → 0, as well as in J = 2 → 1 spectral lines (e.g. Bitran et al 1997;Dahmen et al 1998;Oka et al 2001). Up to now, there are few complete maps in species that are less abundant than CO (e.g.…”
Section: Introductionmentioning
confidence: 99%